2022
DOI: 10.1111/epi.17292
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic biomarkers in children with drug‐resistant epilepsy on various types of ketogenic diet therapies: A cross‐sectional study

Abstract: Objective: This study was undertaken to determine the hemoglobin A1c (HbA1c) and modified glucose-ketone index (mGKI) in children on different types of ketogenic diet (KD) for treatment of drug-resistant epilepsy, with attempts to evaluate their relationships with components of diet regime and other biomarkers. Methods:We conducted a cross-sectional study in children with drug resistant epilepsy aged between 6 months and 18 years, who were on various types of KD therapies without any change in regime for at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The consensus on KD from the China Association Against Epilepsy regarding the optimal state of ketosis suggests that urine ketone level should be maintained above 3, blood ketone level should be 1.2-4.9 mmol/L, blood glucose level should be controlled at approximately 4.0 mmol/L, and blood glucose/ketone ratio (glucose/ketone index) should be 1:1-2:1. 10 Because the definition of ketosis varies, some studies maintained a goal of a serum BHB level of 4-6 mmol/L in refractory epilepticus (RE) patients, 24 some maintained a goal of >2-3 mmol/L in SRSE patients, 25,26 and some maintained a goal of ≥1.5 mmol/L in FIRES/SRSE patients. 27 From these studies, we can see that the BHB value in FIRES patients was lower than that in RE and SRSE patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consensus on KD from the China Association Against Epilepsy regarding the optimal state of ketosis suggests that urine ketone level should be maintained above 3, blood ketone level should be 1.2-4.9 mmol/L, blood glucose level should be controlled at approximately 4.0 mmol/L, and blood glucose/ketone ratio (glucose/ketone index) should be 1:1-2:1. 10 Because the definition of ketosis varies, some studies maintained a goal of a serum BHB level of 4-6 mmol/L in refractory epilepticus (RE) patients, 24 some maintained a goal of >2-3 mmol/L in SRSE patients, 25,26 and some maintained a goal of ≥1.5 mmol/L in FIRES/SRSE patients. 27 From these studies, we can see that the BHB value in FIRES patients was lower than that in RE and SRSE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the classical KD results in higher blood ketone level than a modified Atkins diet. 24 We found that two patients (S-3, S-8) had a lower level of ketosis (BHB 1-2 mmol/L, urine ketone 2þ) even with the classical 4:1 KD but their SE stopped, and they regained consciousness and could be taken off the ventilator, which was similar to the result of the study in which two SRSE patients got benefits at lower levels of ketosis (neither urine ketone ≥2þ nor serum B O H ≥ 2 mmol/L). 26 This finding may suggest that low level of ketosis may still reach the threshold for seizure control for a few FIRES patients.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy research indicates that glucose ketone index may be more strongly correlated to seizure control than either ketone or glucose level alone. 24, 25 In an analysis of GKI we observed covariation and significant granger causality between GKI level and mood (Z = 2.32, p < 0.05), energy (Z = 2.28, p < 0.05) and anxiety (44.51, p < 0.001) and particularly in the responder group who remained on the diet (mood (Z = 3.11 p < 0.01), energy (Z = 3.60 p < 0.001) and anxiety (Z = 55.14 p < 0.001)). The GKI plots exhibit further evidence of an adaptation period where mood and energy increase as GKI falls (indicating an increasing ratio of ketones to glucose).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the blood ketone levels did not proportionately correlate with KD efficacy. 2 Therefore, we did not analyze the relationship between ketone levels and the effect on seizure control in this study. To ensure the homogeneity of research, for patients enrolled in 2011, we retrospectively reclassified them according to the ILAE 2017 classification.…”
Section: Response To "Pediatric Refractory Epilepsy: Exploring the Ke...mentioning
confidence: 98%